Alliance of enemies : the untold story of the secret American and German collaboration to end World War II - Von Hassell, Agostino 1953- (Thomas Dunne books, 2006)
"Alliance of enemies tells the history of the secret World War II relationship between Nazi Germany's espionage service, the Abwehr, and the American OSS, predecessor of the CIA